PEMANFAATAN MICROSOFT SWAY SEBAGAI E-LKPD PADA MATERI SISTEM SIRKULASI DARAH - Mila Wintriani; Dasrieny Pratiwi; Agus Sujarwanta (EDUBIOLOCK, 2026)
The investigation sought to reveal how the incorporation of Microsoft Sway within lessons on the human circulatory system influences learners’ critical reasoning abilities. An experimental framework was employed, emphasizing the integration of an electronic worksheet (E-LKPD) designed with Microsoft Sway into classroom activities. Participants consisted of eleventh-grade science students at SMA Kartikatama Metro. Information was obtained through assessments of critical reasoning as well as questionnaires capturing learners’ perceptions. Analysis demonstrated a notable rise in critical reasoning performance, reflected in an average N-Gain score of 0.728, categorized as “High.” Furthermore, questionnaire responses yielded an average score of 94.6%, signifying that learners viewed the use of Microsoft Sway in studying the circulatory system very positively. These outcomes affirm that the Microsoft Sway-based E-LKPD serves as a practical and effective medium for biology instruction, while simultaneously fostering the enhancement of students’ critical reasoning capacity.